2013
DOI: 10.1264/jsme2.me13049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of <i>Azospirillum</i> sp. B510 Inoculation on Rice-Associated Bacterial Communities in a Paddy Field

Abstract: Rice seedlings were inoculated with Azospirillum sp. B510 and transplanted into a paddy field. Growth in terms of tiller numbers and shoot length was significantly increased by inoculation. Principal-coordinates analysis of rice bacterial communities using the 16S rRNA gene showed no overall change from B510 inoculation. However, the abundance of Veillonellaceae and Aurantimonas significantly increased in the base and shoots, respectively, of B510-inoculated plants. The abundance of Azospirillum did not differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…strains produce siderophores, and some of them can produce cyanhydric acid and solubilize phosphorus as well as increase the plant height, the number of leaves, the stem diameter of rice and maize plants; and the number of grains and the total weight of maize grains. The results were also supported by the results of Isawa et al (2010) and Bao et al (2013), who reported a significant enhancement of rice growth in terms of tiller numbers, shoot length and shoot biomass consecutive to rice seed inoculation with Azospirillum B510, under greenhouse and field conditions. Pandiaranja and Govindara (2012) reported that the strains of Azospirillum help the plants for better growing by means of utilization of various parameters from the soil to the plants.…”
Section: Discussionsupporting
confidence: 78%
“…strains produce siderophores, and some of them can produce cyanhydric acid and solubilize phosphorus as well as increase the plant height, the number of leaves, the stem diameter of rice and maize plants; and the number of grains and the total weight of maize grains. The results were also supported by the results of Isawa et al (2010) and Bao et al (2013), who reported a significant enhancement of rice growth in terms of tiller numbers, shoot length and shoot biomass consecutive to rice seed inoculation with Azospirillum B510, under greenhouse and field conditions. Pandiaranja and Govindara (2012) reported that the strains of Azospirillum help the plants for better growing by means of utilization of various parameters from the soil to the plants.…”
Section: Discussionsupporting
confidence: 78%
“…Understanding the bacterial response to increased [CO 2 ] is necessary to predict its effects on the rice and paddy ecosystem because rice-associated bacteria produce plant hormones, fix nitrogen, and oxidize methane (Bao et al, 2014 ; Ikeda et al, 2014 ). The relative abundances and activities of these bacteria are affected by field management (Bao et al, 2013 , 2014 ; Ikeda et al, 2014 ), rice genotype (Sasaki et al, 2013 ; Okubo et al, 2014a ), and growth stage (Okubo et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the flooding time in rice fields, low farmer income, environment pollution as well as overuse of chemical nitrogen fertilizers. Several effective nitrogen fixing bacteria have been applied successfully in developing countries such as Azospirillum brasilense, Azopspirillum lipoferum (Bao et al 2013); Pseudomonas stutzeri (Vermeiren et al 1999), Herbaspirillum seropedicae (James et al 2002). The results from these experiments varied due to different ISSN: 2320-5407 Int.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%